Theobromine for the treatment of persistent cough: a randomised, multicentre, double-blind, placebo-controlled clinical trial - Morice, A; McGarvey, L; Pavord, I; Higgins, B; Chung, K; Birring, S (AME Publishing Company, 2017)
Background To investigate the effect of BC1036 on health-related quality of life (QOL) in subjects with persistent cough. The secondary objective was to investigate the effect of BC1036 on subjective cough severity. Methods This was a randomised, multicentre, double-blind, placebo-controlled, parallel-group study in 289 subjects with persistent cough. Subjects received BC1036 or placebo twice daily for 14 days. The primary endpoint comprised cough-related QOL assessed using the validated Leicester Cough Questionnaire (LCQ) at Day 14. Secondary endpoints comprised the LCQ scores at Day 7 and Day 28, cough severity VAS scores at each visit and pulmonary function tests. Results At baseline, mean total LCQ score in the BC1036 group was lower (i.e., worse QOL) than placebo (P<0.001), indicating significant between-group heterogeneity. Mean baseline-adjusted change in LCQ score at Day 14 was greater for BC1036 [mean (SD) 2.4±3.5] compared to placebo [mean (SD) score 2.2±3.0], but did not reach statistical significance (P=0.60). Mean cough severity VAS score decreased to a greater extent in the BC1036 group compared to placebo, but again the results were not statistically significant (−12.2±23.28 in BC1036 group and −11.0±21.34 in placebo group at Day 14, P=0.688). There was no significant change in pulmonary function measurements. The adverse event (AE) profile was similar in both groups. Conclusions This study showed that BC1036 was well tolerated and, although the primary endpoint did not achieve statistical significance, the magnitude of improvement was greater with BC1036 compared to placebo with respect to improving QOL and reducing cough severity.